EFFECT OF CONVENIENCE AND TRUST TIKTOK SHOP ONLINE PURCHASE DECISIONS - Taan, Hapsawati (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
Current technological developments encourage many people to make purchasing decisions onlineonline. This research aims to determine 1) the influence of convenience on Tiktok Shop online purchasing decisions, 2) the influence of trust on Tiktok Shop online purchasing decisions. The population in this study were students from the Faculty of Economics, Gorontalo State University who made online purchases at the TikTok shop. The sampling technique method usesnonprobability sampling with methodpurposive sampling. The total sample was 97 respondents. Data collection was carried out by distributing questionnaires viagoogle form. The data analysis method uses the Multiple Linear Regression Test with the help of SPSS version 20. Based on the results of the data analysis, it can be concluded that: 1) Convenience does not have a significant effect on online TikTok shop purchasing decisions for students at the economics faculty at Gorontalo State University. 2) Trust has a significant effect on online TikTok shop purchasing decisions among students at the Faculty of Economics, Gorontalo State University. 4) Convenience and trust simultaneously influence online TikTok shop purchasing decisions among students at the Faculty of Economics, Gorontalo State University.